Nekara Pejeng: Representasi Peninggalan Karya Seni Zaman Praaksara Bali - Ida Bagus Brata; I Komang Sudirga; I Ketut Laba Sumarjiana (Mudra Jurnal Seni Budaya, 2022)
This paper was compiled based on the results of a study to identify and understand the Nekara Pejeng artifact as a representation of the heritage of Balinese pre-literacy. The conducted study belongs to qualitative research with settings according to the condition of the subject. This research was carried out through a literature review approach and data studies through computer networks, such as social media and the internet, combined with field studies by visiting Penataran Sasih Temple where nekara is kept as cultural objects, which was also the research locus. Primary data was obtained through direct observation by visiting the object of research in addition to conducting interviews with a number of informants who had been determined before the research activity began. Secondary data were obtained through literature review in order to collect expert opinions that have been stated in books, accompanied by writings in various journals, results of seminars and workshops, as well as social media. The secondary data here were complementary to the primary data. This is due to studies in the research carried out being closer or more comprehensive. This study aimed to provide a clearer picture of Nekara Pejeng as a work of art from the Balinese pre-literacy era so that the method used was more descriptive qualitative. Because of its qualitative nature, the researcher is the main instrument, supported by interview guidelines in the form of a list of questions to guide the interview with informants such as Gedong Arca Bedaulu Gianyar Museum officers, Pejeng Village Heads, Village Prajuru (staff), temple administrators, community leaders who were purposively selected. This study proved that the moon of Pejeng is a bronze drum (nekara) stored in Penataran Sasih Temple which is believed by the Balinese to have supernatural powers and is used by the community in ceremonies asking for rain. The characteristics of Nekara Pejeng are in the form of a drum/drum made of bronze, there is a waist pattern in the middle, equipped with two sides of the punch field, and one of the fields is open. The moon of Pejeng is the largest nekara discovery in Asia which can represent the advancement of technology and art in the Balinese pre-literacy era. The decoration on the nekara contains magical religious meanings, namely local wisdom in the form of beautiful works of art with high aesthetics as evidence of the creativity of Balinese people in art which began in the pre-literacy period, continues to grow, develop, and have dynamics to this day.